FOOD IDIOMS IN ENGLISH: A LINGUACULTURAL APPROACH - Makhmudova Sabinabonu (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This text introduces the Linguocultural Approach to language study, emphasizing the inseparable connection between language and culture. It defines language as both a product and shaper of culture, highlighting how it embodies cultural values, beliefs, and history. The approach focuses on the cultural background reflected in linguistic units and precedent texts. The text stresses the critical importance of this approach for understanding idioms, which are presented as deeply embedded in cultural contexts and history. It defines idioms as figurative expressions whose meaning differs from the literal words. The text then specifically applies the linguocultural approach to English food idioms, detailing how to examine their cultural origin, embedded values, the link between literal and figurative meanings, and cross-cultural comparisons.